Peran Badan Pemulihan Aset di Kejaksaan Negeri Donggala - Andika Maulana Syah Putra; Ronny Max Hendra; Rato, Dominikus; Ohoiwutun, Y.A. Triana (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This research explains the role of the Asset Recovery Agency (formerly known as the "Asset Recovery Center") at the Donggala District Attorney's Office. In Law Number 16 of 2004 concerning the Attorney General's Office of the Republic of Indonesia jo. Law Number 11 of 2021 concerning Amendments to Law Number 16 of 2004 concerning the Attorney General's Office of the Republic of Indonesia in Article 2 paragraph (1) essentially states that the Attorney General's Office of the Republic of Indonesia is a government institution that exercises state power in the field of prosecution and other authorities based on the law. The research results show that the purpose of the establishment of the Asset Recovery Agency (formerly known as the "Asset Recovery Center") at the Donggala District Attorney's Office is based on the principles of social justice and legal certainty as stipulated by the Prosecutor's Law, whereby the return of assets to the rightful owners or to the State is carried out to achieve this goal, thereby providing a deterrent effect on criminal offenders. Because the illegal acquisition of something or an asset, the asset recovery handling procedure at the Donggala District Attorney's Office is carried out in accordance with the laws and regulations but lacks transparency, as evidenced by the absence of socialization of the Asset Recovery Center (PPA) or Asset Recovery Agency (BPA) to the general public both online and offline. As a result, the general public will have difficulty accessing information regarding the clarity of the status of confiscated goods or assets related to criminal offenses managed by the prosecutor's office. The author believes this because, based on a comparison with the Asset Recovery Center (PPA) and the Asset Recovery Agency (BPA) of the Donggala District Attorney's Office and the Palu District Attorney's Office, information regarding the Asset Recovery Center (PPA) and the Asset Recovery Agency (BPA) and Standard Operating Procedures (SOP) is easily accessible online. To achieve this goal, the PPA and BPA should innovate so that the public can easily access the information provided by the prosecutor's office.